Guide for authors: jCEC Template 2023 - Antonio Marcos de Oliveira Siqueira; Ivan Carlos Franco (The Journal of Engineering and Exact Sciences)
This document gives formatting instructions for authors preparing articles for publication in the jCEC journal.  The authors must follow the instructions given in the document for the articles to be published.  You can use this document as both an instruction set and as a template into which you can type your own text. Abstract should be no longer than 1000 characters including spaces (or from 200 to 300 words). It gives a brief summary of the content of the main objective, the methods, the results obtained and major conclusions. Translation of the abstract to an appropriate language must be provided here. Please choose either Portuguese or Spanish, and adapt your list of keywords accordingly.